2019
DOI: 10.4103/ijmr.ijmr_635_18
|View full text |Cite
|
Sign up to set email alerts
|

Safety & efficacy of an intravasal, one-time injectable & non-hormonal male contraceptive (RISUG)

Abstract: Background & objectives:For improved male contraception, a new polymeric drug molecule – Reversible Inhibition of Sperm under Guidance (RISUG) has been synthesized and has been found to be effective, safe and reversible in various animal species. Phase-I and phase-II clinical trials have confirmed its safety and contraceptive efficacy. The present study was undertaken as a multicentric-limited phase-III clinical trial to test the efficacy and safety of RISUG in human volunteers.Methods:One hundred and thirty n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Several clinical trials of RISUG in men in India have been performed. [23][24][25] These studies showed excellent contraceptive efficacy over periods of up to 1 year. However, data on efficacy and reversibility from large-scale clinical trials have not been published, leading to concern about the reversibility of the procedure.…”
Section: Reversible Vas Occlusionmentioning
confidence: 81%
“…Several clinical trials of RISUG in men in India have been performed. [23][24][25] These studies showed excellent contraceptive efficacy over periods of up to 1 year. However, data on efficacy and reversibility from large-scale clinical trials have not been published, leading to concern about the reversibility of the procedure.…”
Section: Reversible Vas Occlusionmentioning
confidence: 81%
“…Few subjects were reported to be lost in follow up due to personal reasons, 0.3% method failure and 0.98% overall failure in efficacy of the drug has been observed [53]. A multi-centric limited Phase III clinical trial of RISUG ® reported no pregnancy among the subjects that received complete dose of RISUG ® and indicated it is an effective and safe male contraceptive with majority of the individuals under study achieving either oligozoospermia or azoospermia within 2 months after injection [56].…”
Section: Clinical Journeymentioning
confidence: 99%
“…RISUG is an injectable medicine consisting of a copolymer of maleic anhydride styrene chemically reacted with dimethyl sulfoxide. In studies [22] on 139 men who were given 120 μl of RISUG as bilateral vas intraluminal injection. Six men had a procedure error and did not achieve azoospermia, while the remaining 133 had severe oligospermia or azoospermia.…”
Section: Non-hormonal Male Contraceptivesmentioning
confidence: 99%